Presence of neuroticism and antidepressant remission rates in late-life depression: results from the Neurobiology of Late-Life Depression (NBOLD) study. (4th December 2017) - Steffens, David C.; Wu, Rong; Grady, James J.; Manning, Kevin J.
ABSTRACT: Neuroticism in older adults is common yet understudied, particularly its effects on depression treatment outcomes. We hypothesized that presence of high neuroticism would be associated with lower 12-week remission rates in older depressed sertraline-treated patients. In this longitudinal cohort study, 43 depressed older adults completed the Revised NEO Personality Inventory (NEO PI-R). A study psychiatrist administered the Montgomery Ǻsberg Depression Rating Scale (MADRS), and the Cumulative Illness Rating Scale (CIRS, a measure of medical burden) at baseline, and the MADRS at each clinical visit. All subjects began open-label sertraline treatment and were followed over 12 weeks with clinically indicated flexible dosing and an option to switch antidepressants. We used regression analyses to examine factors related to 12-week remission of depression (MADRS score < 8) and final MADRS score. We found that higher total neuroticism (odds ratio (OR) = 0.963, 95% confidence interval (CI) = 0.928–1.000) and a neuroticism subscale, stress vulnerability (OR = 0.846, 95% CI = 0.728–0.983), were associated with lower likelihood of remission among both the intention-to-treat group and sertraline completers. Findings remained significant after controlling for baseline MADRS and CIRS score. In conclusion, assessment of personality, particularly features of neuroticism, may be important in management of late-life depression. Future studies should determine if depressed patients high in neuroticism may benefit from psychotherapy focusing on emotional regulation and stress management.